Handbook of soil sciences : resource management and environmental impacts - Huang, P. M.; Li, Yuncong; Sumner, M. E. (Malcolm E.), 1933- (Handbook of Soil Science., 2011)
An evolving, living organic/inorganic covering, soil is in dynamic equilibrium with the atmosphere above, the biosphere within, and the geology below. It acts as an anchor for roots, a purveyor of water and nutrients, a residence for a vast community of microorganisms and animals, a sanitizer of the environment, and a source of raw materials for construction and manufacturing. To develop lasting solutions to the challenges of balanced use and stewardship of the Earth, we require a fundamental understanding of soil-from its elastic, porous three-phase system to its components, processes, and re.